A dual‐band dual‐polarized cubical DRA coupled with new modified cross‐shaped slot for ISM (2.4 GHz) and Wi‐MAX (3.3‐3.6 GHz) band applications. Issue 1 (8th October 2018) - Kumar, Rajkishor; Chaudhary, Raghvendra Kumar
Abstract: In this article, a new modified cross‐shaped coupled cubical dielectric resonator antenna (DRA) has been investigated for dual‐band dual‐polarized applications. The linearly polarized (LP) fields in DRA has been generated by using a single slot in the ground plane and kept at either 45° ( S L1 ) or −45° ( S L2 ) from the microstrip feed line. Combining these two slots ( S L1 and S L2 ) in the modified ground plane, the proposed structure able to generate circularly polarized (CP) field in DRA. But the generated CP field is not enough to cover ISM 2400 band. To achieve CP in ISM 2400 band, an extra slot ( S L3 ) to the existing slots and an extra strip ( S T ) in the circular ring feed line have been included. This modified final antenna arrangement has been able to produce LP (due to loading effect, ie, slot and DRA) and CP fields (orthogonal modes have been generated, ie, TE x 111 and TE y 111 ), simultaneously. The measured CP and LP, −10 dB impedance bandwidths are 11.85% (2.38‐2.68 GHz) and 9.11% (3.25‐3.56 GHz) in combination with the 3‐dB axial ratio bandwidth of 4.11% (2.38‐2.48 GHz). The generated CP and LP fields are used for different wireless communication bands such as ISM 2400 and Wi‐MAX (3.3‐3.7 GHz) bands.